Selective deglycosylation of lactoferrin to understand glycans’ contribution to antimicrobial activity of lactoferrin - Karav, Sercan (Cellular and Molecular Biology, 2018)
Lactoferrin is a highly glycosylated antimicrobial protein that contains multiple glycan types. In this research, recombinantly produced three forms of novel endo-Î²-N-acetylglucosaminidase (free, genetically attached Glutatiohine-S-transferase and polyhistide) were used for selective release of lactoferrin glycans to understand the contribution of specific glycan types to the antimicrobial function of lactoferrin. Three lactoferrin forms with different glycan profile were obtained by treatment with these fusion tagged enzymes; native, fully deglycosylated and sialylated glycan enriched lactoferrin. The released glycan structures were analyzed and confirmed with mass spectrometry. The results showed that native and sialylated glycans enriched lactoferrin have similar minimum inhibitory concentration (MIC) values against E.coli DH5a (1 mg/ml), whereas the MIC value for fully deglycosylated lactoferrin was 6mg/ml. These results suggest that sialylated glycans play important role in the antimicrobial function of lactoferrin.